2017
DOI: 10.1161/atvbaha.117.309307
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of Interleukin 1-Receptor Antagonist and Risk of Cardiovascular Disease

Abstract: Serum IL-1RA levels were positively associated with risk of CVD after adjustment for multiple confounders in a meta-analysis of 6 population-based cohorts. This association may at least partially reflect a response to triggers inducing subclinical inflammation, oxidative stress, and endothelial activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 35 publications
4
52
0
1
Order By: Relevance
“…It might be surprising that high SFRP5 was associated with lower levels of the anti-inflammatory IL-1Ra which argues against an anti-inflammatory action of SFRP5 at a first glance. However, prospective studies clearly demonstrated that higher IL-1Ra levels were associated with a higher risk of type 2 diabetes and cardiovascular events [3335]. This association may at least partially reflect a response to proatherogenic factors such as subclinical inflammation (including IL-1β-mediated processes, which upregulate IL-1Ra) and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…It might be surprising that high SFRP5 was associated with lower levels of the anti-inflammatory IL-1Ra which argues against an anti-inflammatory action of SFRP5 at a first glance. However, prospective studies clearly demonstrated that higher IL-1Ra levels were associated with a higher risk of type 2 diabetes and cardiovascular events [3335]. This association may at least partially reflect a response to proatherogenic factors such as subclinical inflammation (including IL-1β-mediated processes, which upregulate IL-1Ra) and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent meta-analysis has shown a positive association between higher serum levels of IL-1 receptor antagonist and increased incidence of cardiovascular disease in the general population. 56 Based on the inflammatory hypothesis of atherosclerotic cardiovascular diseases, a large-scale randomized clinical trial is currently ongoing to elucidate whether targeting IL-1β can reduce the risk of recurrent cardiovascular events (the CANTOS trial [canakinumab anti-inflammatory thrombosis outcomes study]). 57 A novel link between inflammation and coronary endothelial dysfunction has been reported from the Lerman laboratory; human coronary endothelial dysfunction was more severe in coronary artery segments with macrophage infiltration and vasa vasorum proliferation in an additive manner than in those without them, indicating an important role of inflammation and vasa vasorum proliferation in the pathogenesis of coronary artery disease.…”
Section: Hallmark Of Disease Inflammationmentioning
confidence: 99%
“…In DPN, increased IL-1RA levels reflect compensatory upregulation in response to IL-1b dysregulation with low-grade inflammatory diseases. Recombinant IL-1RA and IL-1b inhibitor used in clinical trials were required for clarification of the inflammatory process role in the progression of DPN 7 .…”
mentioning
confidence: 99%